2020
DOI: 10.1016/j.celrep.2020.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for Rac1 in Sertoli Cell Function during Testicular Development and Spermatogenesis

Abstract: Sertoli cells are supporting cells of the testicular seminiferous tubules, which provide a nurturing environment for spermatogenesis. Adult Sertoli cells are polarized so that they can simultaneously support earlier-stage spermatogenic cells (e.g., spermatogonia) basally and later-stage cells (e.g., spermatids) apically. To test the consequences of disrupting cell polarity in Sertoli cells, we perform a Sertoli-specific conditional deletion of Rac1, which encodes a Rho GTPase required for apicobasal cell polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 55 publications
3
31
1
Order By: Relevance
“…Sertoli cell-formed BTB is polarized, which separates earlier-stage spermatogenic cells basally and later-stage cells apically within the seminiferous epithelium of adult testes 11 . Recently, it was revealed that Rac1 deficiency in Sertoli cells was correlated with defects in cell polarity, which was manifested by the mis-localization of polarity proteins and the disruption of the BTB 20 . While the mechanism remained elusive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sertoli cell-formed BTB is polarized, which separates earlier-stage spermatogenic cells basally and later-stage cells apically within the seminiferous epithelium of adult testes 11 . Recently, it was revealed that Rac1 deficiency in Sertoli cells was correlated with defects in cell polarity, which was manifested by the mis-localization of polarity proteins and the disruption of the BTB 20 . While the mechanism remained elusive.…”
Section: Resultsmentioning
confidence: 99%
“…Within the Rho GTPases family, Rac1 has been most extensively characterized 18 . Recently, Rac1 has been demonstrated to be required for Sertoli cell polarity and BTB integrity during later stages of spermatogenesis 20 . Although Rac1 is dispensable for the establishment and maintenance of undifferentiated spermatogonia and for fetal testis differentiation, Sertoli Rac1 in adult testis is required for later stages of spermatogenesis and spermiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the role of Cdc42 in Sertoli cells in vivo, Cdc42 conditional knockout mice were generated using Dhh-Cre (referred to as "cKO" hereafter), which we recently confirmed is highly specific and effective for targeting Sertoli cells starting as early as E12.5 (Heinrich et al, 2020). Previously published cell-type-specific and single-cell transcriptome studies indicated that Cdc42 is highly expressed in multiple testicular cell types, including Sertoli cells, starting at the earliest stages of testicular differentiation until adulthood (Figures S1A-S1D) (Green et al, 2018;Jameson et al, 2012;Stevant et al, 2018).…”
Section: Cdc42 In Sertoli Cells Is Essential For Adult Steady-state Spermatogenesismentioning
confidence: 99%
“…Here, we report a lower number of Sertoli cells in cKO seminiferous tubules. Although Sertoli cells regulate the number of germ cells and Leydig cells during testicular development (Rebourcet et al, 2017;Heinrich et al, 2020), a postnatal effect on the number of PMCs has not been reported. Given that the proliferation of PMCs takes place earlier than that of Sertoli cells when induced by neonatal hemicastration or administration of follicle stimulating hormone (Nurmio et al, 2012) and that Sertoli cell ablation in neonatal testis with benzalkonium chloride does not affect the number of PMCs in vitro (Yokonishi et al, 2020), it is possible that the number of Sertoli cells is affected by testicular smooth muscle cells in postnatal testicular development.…”
Section: Testicular Smooth Muscle Cells Might Affect Numbers Of Sertomentioning
confidence: 99%